Lithium nickel cobalt borate positive electrode material and preparation method thereof

By using lithium cobalt oxide in the surface and cladding layer of the nickel-cobalt lithium borate positive electrode material, the problems of poor performance and large interface impedance under high temperature conditions are solved, and better high-temperature performance and cycling performance are achieved.

CN119674017APending Publication Date: 2025-03-21BATTEROTECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411885896.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Nickel-cobalt lithium borate positive electrode material has poor performance under high temperature conditions and has a large interface impedance, which affects the internal resistance and cycling performance of lithium-ion batteries.

Method used

By using lithium cobalt oxide in the surface layer and the cladding layer of the nickel-cobalt lithium borate positive electrode material, compatibility between the inner layer and the cladding layer is formed, interface impedance is reduced, and side reactions between the positive electrode material and the electrolyte are reduced under high temperature conditions.

Benefits of technology

It improves the high-temperature performance of the nickel-cobalt lithium borate positive electrode material, reduces the interface impedance, and enhances the cycling performance and electronic conductivity of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674017A_ABST
    Figure CN119674017A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion battery positive electrode materials, in particular to a nickel cobalt lithium borate positive electrode material and a preparation method thereof. The lithium nickel cobalt borate positive electrode material comprises a body and a coating layer, the body comprises an inner layer and a surface layer, the inner layer is made of lithium nickel cobalt borate, and the surface layer is made of lithium cobalt oxide; the coating layer is coated on the surface of the surface layer, and the material of the coating layer is lithium cobalt oxide. Based on the lithium nickel cobalt borate positive electrode material provided by the invention, the lithium cobalt oxides on the surface layer and the surface of the body form an isolation barrier between the inner layer of the positive electrode material and the electrolyte, so that the side reaction of the inner layer of the positive electrode material and the electrolyte under a high-temperature condition can be reduced, and the high-temperature performance of the positive electrode material can be enhanced. And the surface layer and the coating layer have the same material structure, so that the compatibility between the body of the lithium nickel cobalt borate positive electrode material and the interface of the coating layer is relatively good, and the interface impedance is favorably reduced. In addition, the electronic conductivity of the positive electrode material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of positive electrode materials for lithium-ion batteries, and in particular to a nickel-cobalt-lithium borate positive electrode material and a preparation method thereof. Background Art

[0002] As a positive electrode material, lithium nickel cobalt borate has a high capacity, but poor high temperature performance. In order to solve the problem of poor high temperature performance of lithium nickel cobalt borate, it is surface coated to reduce the side reaction between lithium nickel cobalt borate and electrolyte. In the prior art, the interface impedance of lithium nickel cobalt borate positive electrode material with coating layer is very large, which is not conducive to reducing the internal resistance of lithium ion battery. Summary of the invention

[0003] The present application provides a nickel cobalt lithium borate positive electrode material and a preparation method thereof, which can solve the technical problems of poor high temperature performance and large interface impedance of the existing nickel cobalt lithium borate positive electrode materials.

[0004] The technical solutions of this application are as follows:

[0005] In the first aspect, the present application provides a nickel cobalt lithium borate positive electrode material, including a main body and a coating layer, the main body includes an inner layer and a surface layer, the material of the inner layer is nickel cobalt lithium borate, and the material of the surface layer is lithium cobalt oxide; the coating layer is coated on the surface of the surface layer, and the material of the coating layer is lithium cobalt oxide.

[0006] Based on the nickel cobalt lithium borate positive electrode material provided in the present application, when the positive electrode material is used in a lithium-ion battery, since the surface layer of the main body has lithium cobalt oxide, and the surface of the main body has a coating layer of lithium cobalt oxide, the surface layer of the main body and the lithium cobalt oxide on the surface form an isolation barrier between the inner layer of the positive electrode material and the electrolyte. In this way, the side reaction between the inner layer of the positive electrode material and the electrolyte under high temperature conditions can be reduced, thereby helping to enhance the high temperature performance of the positive electrode material.

[0007] Secondly, the nickel cobalt lithium borate positive electrode material provided in the present application has a main body surface material of lithium cobalt oxide, and a coating layer of lithium cobalt oxide. The material structure of the surface layer and the coating layer is the same. Therefore, the main body of the nickel cobalt lithium borate positive electrode material and the coating layer interface have good compatibility, which helps to reduce the interface impedance.

[0008] In one possible design, the median particle size D50 of the inner layer is 2-15 μm.

[0009] Based on the positive electrode material provided in this embodiment, when the median particle size D50 of the inner layer is in the range of 2-15 μm, the inner layer is easy to realize, not easy to break, and the cycle performance is relatively stable.

[0010] In one possible design, the surface layer has a thickness of 1-100 nm.

[0011] Based on the positive electrode material provided in this embodiment, the thickness of the surface layer is 1-100 nm, which not only helps to enhance the high temperature performance of the positive electrode material, but also takes into account the ionic conductivity and electronic conductivity of the positive electrode material.

[0012] In one possible design, the coating layer has a thickness of 1-100 nm.

[0013] The positive electrode material provided based on this embodiment not only helps to enhance the high temperature performance of the positive electrode material, but also takes into account the ionic conductivity and electronic conductivity of the positive electrode material.

[0014] In the second aspect, based on the same inventive concept, the present application also provides a method for preparing a nickel cobalt lithium borate positive electrode material, comprising the following steps:

[0015] S1) provides a nickel-cobalt-boron matrix with a molecular formula of Ni x Co y B z (OH)2, x+y+z=1;

[0016] S2) forming Co(OH)2 on the surface of the NiCoB matrix;

[0017] S3) using a substance with a surface layer of Co(OH)2 and an inner layer of a nickel-cobalt-boron matrix as a precursor, mixing the precursor with an excess of lithium salt, and pre-sintering to form nickel-cobalt-borate lithium borate in the inner layer and lithium cobaltate in the surface layer, and the product is in a block shape;

[0018] S4) crushing the block product obtained in step S3) to obtain a granular pre-sintered semi-finished product with an inner layer of nickel cobalt lithium borate and a surface layer of lithium cobalt oxide;

[0019] S5) mixing the product obtained in step S4) with a cobalt salt and sintering the mixture, so that the cobalt salt reacts with the lithium salt remaining on the surface of the granular pre-sintered semi-finished product, thereby forming a coating layer of lithium cobalt oxide on the surface of the granular pre-sintered semi-finished product.

[0020] Based on the preparation method of the nickel cobalt lithium borate positive electrode material provided in the second aspect, a positive electrode material body with an inner layer of nickel cobalt lithium borate and a surface layer of lithium cobalt oxide can be formed through steps S2) and S3). On this basis, step S5) is cleverly designed, and step S5) can not only remove the impurities introduced by the previous preparation steps, but also form a coating layer with good ionic conductivity on the surface of the positive electrode material body, and the material of the coating layer is the same as the material of the surface layer of the body, thus reducing the interface impedance of the positive electrode material.

[0021] In a possible design, in step S2), the method used to form Co(OH)2 on the surface of the nickel-cobalt-boron matrix is ​​a co-precipitation method.

[0022] In one possible design, in step S2), the cobalt salt used to form Co(OH)2 includes at least one of CoCl2·6H2O, Co(CH3COO)2·4H2O, CoCO3, Co(NO3)2·6H2O, CoSO4·7H2O, CoO, Co2O3, Co3O4, Co(OH)2, and CoC2O4.

[0023] Based on the preparation method of nickel cobalt lithium borate positive electrode material provided in this embodiment, the listed CoCl2·6H2O, Co(CH3COO)2·4H2O, CoCO3, Co(NO3)2·6H2O, CoSO4·7H2O, CoO, Co2O3, Co3O4, Co(OH)2, and CoC2O4 are all water-soluble compounds, which can form cobalt ions in aqueous solution, thus facilitating the formation of Co(OH)2 precipitation.

[0024] In a possible design, in step S2), the precipitant used in the co-precipitation method includes at least one of KOH, NaOH, LiOH or ammonia water.

[0025] In one possible design, in step S5), the cobalt salt is at least one of Co(CH3COO)2·4H2O, CoCO3, Co(NO3)2·6H2O, CoSO4·7H2O, CoO, Co2O3, Co3O4, Co(OH)2, CoC2O4, and MgCo(OH)4.

[0026] In a possible design, in step S2), the coating thickness of Co(OH)2 is 1-100 nm.

[0027] Based on the preparation method of nickel cobalt lithium borate positive electrode material provided in this embodiment, in step S2), the coating thickness of Co(OH)2 is controlled to be 1-100nm. Then, in step S3), when Co(OH)2 is mixed and sintered with lithium salt, the thickness of the surface layer of lithium cobalt oxide formed is also about 1-100nm. The beneficial effect of the surface thickness of 1-100nm has been mentioned before and will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a comparison chart of high temperature cycle performance between the first lithium ion battery and the second lithium ion battery.

[0029] Figure 2 A comparison chart of the high temperature storage retention rates of the first lithium ion battery and the second lithium ion battery.

[0030] Figure 3 A comparison chart of the high temperature storage recovery rates of the first lithium ion battery and the second lithium ion battery.

[0031] Figure 4 This is a comparison diagram of the high-temperature storage internal resistance changes of the first lithium-ion battery and the second lithium-ion battery. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments.

[0033] The embodiments given in this application can be combined with each other if no contradiction occurs. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0034] All raw materials used in this application have no particular limitation on their sources and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0035] All raw materials used in the present application, unless otherwise specified, are raw materials commonly used in the art, and those skilled in the art can purchase them commercially or prepare them using conventional methods based on the names of the raw materials and their corresponding uses.

[0036] The abbreviations of the processes used in this application are all conventional abbreviations in the field. The specific steps and conventional parameters of each abbreviation are clear and definite in its relevant field, and those skilled in the art can implement them in a conventional manner based on the abbreviations.

[0037] Unless otherwise defined, all terms used herein have the same meanings as commonly understood by those skilled in the art unless otherwise specified.

[0038] The following is a detailed description of this application.

[0039] As mentioned in the background technology, lithium nickel cobalt borate, as a positive electrode material, has a high capacity, but poor high temperature performance. In order to solve the problem of poor high temperature performance of lithium nickel cobalt borate, it is surface coated to reduce the side reaction between lithium nickel cobalt borate and the electrolyte. However, in the prior art, the coating agent on the surface of lithium nickel cobalt borate will cause the interface impedance of the positive electrode material of lithium nickel cobalt borate to be very large.

[0040] The core idea of ​​the present application is to reduce the interfacial impedance of the nickel cobalt lithium borate positive electrode material by changing the compatibility between the coating layer and the inner layer of the nickel cobalt lithium borate positive electrode material.

[0041] The nickel cobalt lithium borate positive electrode material provided in the present application includes a main body and a coating layer, the main body includes an inner layer and a surface layer, the material of the inner layer is nickel cobalt lithium borate, and the material of the surface layer is lithium cobalt oxide; the coating layer is coated on the surface of the surface layer, and the material of the coating layer is lithium cobalt oxide.

[0042] Based on the nickel cobalt lithium borate positive electrode material provided in the present application, when the positive electrode material is used in a lithium-ion battery, since the surface layer of the main body has lithium cobalt oxide, and the surface of the main body has a coating layer of lithium cobalt oxide, the surface layer of the main body and the lithium cobalt oxide on the surface form an isolation barrier between the inner layer of the positive electrode material and the electrolyte. In this way, the side reaction between the inner layer of the positive electrode material and the electrolyte under high temperature conditions can be reduced, thereby helping to enhance the high temperature performance of the positive electrode material.

[0043] Secondly, the nickel cobalt lithium borate positive electrode material provided in the present application has a main body surface material of lithium cobalt oxide, and a coating layer of lithium cobalt oxide. The material structure of the surface layer and the coating layer is the same. Therefore, the main body of the nickel cobalt lithium borate positive electrode material and the coating layer interface have good compatibility, which helps to reduce the interface impedance.

[0044] In addition, the lithium borate positive electrode material provided in the present application has a surface layer of lithium cobalt oxide and a coating layer of lithium cobalt oxide. Since the electronic conductivity of lithium cobalt oxide is about 10 times that of nickel cobalt lithium borate, the lithium borate positive electrode material provided in the present application has good electronic conductivity.

[0045] In summary, the nickel cobalt lithium borate positive electrode material provided in this application can not only enhance the high temperature performance of the positive electrode material, but also reduce the interface impedance between the main body and the coating layer in the positive electrode material, and also improve the electronic conductivity of the positive electrode material.

[0046] For the nickel cobalt lithium borate positive electrode material provided in this application, since the inner layer less than 2um is difficult to make, the inner layer greater than 15μm has a large particle size and is easy to break, resulting in deterioration of the cycle performance. Therefore, in some embodiments of the present application, the median particle size D50 of the inner layer is 2-15μm. Exemplarily, the median particle size D50 of the inner layer can be 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, or any value between the two adjacent ones. When the median particle size D50 of the inner layer is in the range of 2-15μm, the inner layer is easy to realize, not easy to break, and the cycle performance is relatively stable.

[0047] The thickness of the surface layer has a certain influence on the electronic conductivity, ionic conductivity and high temperature performance of the positive electrode material. Increasing the thickness of the surface layer is conducive to preventing the contact between the electrolyte and the inner layer, which can reduce the side reaction between the inner layer of the positive electrode material and the electrolyte under high temperature conditions and enhance the high temperature performance of the positive electrode material; and increasing the thickness of the surface layer is conducive to enhancing the electronic conductivity of the positive electrode material, but at the same time, too thick a surface layer will affect the transmission of lithium ions. If the thickness of the surface layer is too thin, such as less than 1nm, the surface layer thickness is prone to unevenness.

[0048] In some embodiments of the present application, the thickness of the surface layer is 1-100 nm. Exemplarily, the thickness of the surface layer can be 1 nm, 2 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, or any value between two adjacent ones. In this way, the positive electrode material provided based on this embodiment not only helps to enhance the high temperature performance of the positive electrode material, but also takes into account the ionic conductivity and electronic conductivity of the positive electrode material.

[0049] Based on similar reasons as above, the thickness of the coating layer will also have a certain influence on the electronic conductivity, ionic conductivity and high temperature performance of the positive electrode material.

[0050] In some embodiments of the present application, the coating layer has a thickness of 1-100 nm. Exemplarily, the coating layer may have a thickness of 1 nm, 2 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, or any value between two adjacent layers. Thus, the positive electrode material provided by this embodiment not only helps to enhance the high temperature performance of the positive electrode material, but also takes into account the ionic conductivity and electronic conductivity of the positive electrode material.

[0051] Based on the same inventive concept, the present application also provides a method for preparing a nickel cobalt lithium borate positive electrode material, comprising the following steps:

[0052] S1) provides a nickel-cobalt-boron matrix with a molecular formula of Ni x Co y B z (OH)2, x+y+z=1;

[0053] S2) forming Co(OH)2 on the surface of the NiCoB matrix;

[0054] S3) using a substance with a surface layer of Co(OH)2 and an inner layer of a nickel-cobalt-boron matrix as a precursor, mixing the precursor with an excess of lithium salt, and pre-sintering to form nickel-cobalt-borate lithium borate in the inner layer and lithium cobaltate in the surface layer, and the product is in a block shape;

[0055] S4) crushing the block product obtained in step S3) to obtain a granular pre-sintered semi-finished product with an inner layer of nickel cobalt lithium borate and a surface layer of lithium cobalt oxide;

[0056] S5) mixing the product obtained in step S4) with a cobalt salt and sintering the mixture, so that the cobalt salt reacts with the lithium salt remaining on the surface of the granular pre-sintered semi-finished product, thereby forming a coating layer of lithium cobalt oxide on the surface of the granular pre-sintered semi-finished product.

[0057] Specifically, for step S1), in the present application, the molecular formula of the nickel-cobalt-boron matrix is ​​Ni x Co y B z (OH)2, generally speaking, 0.3≤x≤0.98, 0.01≤y≤0.4, 0.01≤z≤0.4; the nickel-cobalt-boron matrix can be prepared by adding alkali to a nickel-cobalt-boron mixed salt solution and aging it, or it can be purchased.

[0058] For step S3), the mechanism of the process is: during the pre-sintering process, the nickel-cobalt-boron matrix coated with Co(OH)2 on the surface will dehydrate, and the inner layer of the nickel-cobalt-boron matrix and the surface layer of Co(OH)2 will form corresponding oxides. The lithium salt enters the nickel-cobalt-boron matrix from the surface layer through solid phase diffusion. The oxide and the lithium salt react chemically under certain temperature conditions, and the inner layer forms lithium nickel-cobalt borate and the surface layer forms lithium cobaltate. In this process, the excess of lithium salt will be controlled, so that the chemical reaction can be carried out more fully.

[0059] Taking lithium oxide (Li2O) and cobalt oxide (Co3O4) as examples, the reaction equation during calcination is as follows:

[0060] Li2O+Co3O4→2LICoO2;

[0061] In addition to lithium oxide and its hydrate, the lithium salt may also be lithium carbonate, lithium hydroxide and its hydrate. The reaction mechanism of lithium carbonate and cobalt oxide, and the reaction mechanism of lithium hydroxide and cobalt oxide are the same as that of lithium oxide, which will not be described here.

[0062] For step S5), the residual lithium salt in step S3) is an impurity for the positive electrode material. The presence of residual lithium salt will increase the interface impedance of the positive electrode material, increase gas production, and reduce capacity, storage and cycle performance. Step S5) eliminates the residual lithium salt through cobalt salt and generates a new substance, lithium cobaltate. This process not only solves the adverse effects of residual lithium salt as an impurity on the positive electrode material, but also the newly generated substance lithium cobaltate helps to improve the ionic conductivity of the positive electrode material.

[0063] It is understandable that in step S5), the reaction mechanism of the cobalt salt and the residual lithium salt is the same as that in step S3), and will not be repeated here.

[0064] In summary, the preparation method of the nickel cobalt lithium borate positive electrode material provided in the present application can form a positive electrode material body with an inner layer of nickel cobalt lithium borate and a surface layer of lithium cobalt oxide through step S2) and step S3). On this basis, step S5) is cleverly designed. Through step S5), not only can the impurities introduced by the previous preparation steps be removed, but also a coating layer with good ionic conductivity can be formed on the surface of the positive electrode material body, and the material of the coating layer is the same as that of the surface layer of the body, so that the interface impedance of the positive electrode material can also be reduced.

[0065] In some embodiments of the present application, in step S2), the method used to form Co(OH)2 on the surface of the nickel-cobalt-boron matrix is ​​a co-precipitation method.

[0066] Specifically, in this embodiment, when Co(OH)2 is formed on the surface of the nickel-cobalt-boron matrix by the coprecipitation method, it is necessary to prepare a cobalt salt solution and a precipitant, and adjust the pH value of the solution so that the cobalt ions in the solution react with the hydroxide ions to form a Co(OH)2 precipitate on the surface of the nickel-cobalt-boron matrix. After the precipitate is generated, the product can be separated from the mother liquor by filtering or the like, and washed to remove impurities.

[0067] In some embodiments of the present application, in step S2), the cobalt salt used to form Co(OH)2 includes at least one of CoCl2·6H2O, Co(CH3COO)2·4H2O, CoCO3, Co(NO3)2·6H2O, CoSO4·7H2O, CoO, Co2O3, Co3O4, Co(OH)2, and CoC2O4.

[0068] Specifically, in the present application, the coprecipitation method is carried out in a solution, so the cobalt salt used needs to have a certain solubility. The CoCl2·6H2O, Co(CH3COO)2·4H2O, CoCO3, Co(NO3)2·6H2O, CoSO4·7H2O, CoO, Co2O3, Co3O4, Co(OH)2, and CoC2O4 listed in the present application are all water-soluble compounds and can form cobalt ions in aqueous solution, thus facilitating the formation of Co(OH)2 precipitates.

[0069] It should be noted that this embodiment only lists some common cobalt salts currently available. For step S2), all cobalt salts with good solubility are suitable for this application.

[0070] In some embodiments of the present application, the precipitant used in the co-precipitation method includes at least one of KOH, NaOH, LiOH or ammonia water.

[0071] As mentioned above, when Co(OH)2 is formed on the surface of the nickel-cobalt-boron matrix by the coprecipitation method, hydroxide ions are required, and KOH, NaOH, LiOH or ammonia water are all sources of hydroxide ions.

[0072] Among them, KOH, NaOH, and LiOH are strong bases with a high degree of dissociation; ammonia water is a weak base with a low degree of dissociation. The use of strong bases can significantly change the pH value of the solution, and ammonia water can fine-tune the pH value of the solution.

[0073] In some embodiments, only aqueous ammonia may be used as the precipitant. The use of aqueous ammonia can make the precipitation of cobalt more complete.

[0074] In some embodiments, the precipitant may be a combination of any one of KOH, NaOH, and LiOH and aqueous ammonia, which facilitates the control of the reaction.

[0075] In some embodiments of the present application, in step S5), the cobalt salt is at least one of Co(CH3COO)2·4H2O, CoCO3, Co(NO3)2·6H2O, CoSO4·7H2O, CoO, Co2O3, Co3O4, Co(OH)2, CoC2O4, and MgCo(OH)4.

[0076] It should be noted that only some common cobalt salts are listed here. It is understandable that the main function of the cobalt salt required in step S5) is to provide the cobalt element so as to generate lithium cobaltate during calcination with the residual lithium salt. The cobalt salt required in step S5) has no requirement for its solubility, as long as it can provide the cobalt element and does not introduce impurities, and is not limited to the cobalt salts listed here.

[0077] In some embodiments of the present application, in step S2), the coating thickness of Co(OH)2 is 1-100 nm.

[0078] Specifically, in step S2), the thickness of the bulk surface layer in the positive electrode material can be controlled by controlling the coating thickness of the Co(OH)2 precipitate.

[0079] In step S2), the coating thickness of Co(OH)2 is controlled to be 1-100nm. Then, in step S3), when Co(OH)2 is mixed with lithium salt and sintered, the thickness of the surface layer of lithium cobalt oxide formed is also about 1-100nm. The beneficial effect of the surface thickness of 1-100nm has been mentioned before and will not be repeated here.

[0080] In some embodiments of the present application, the lithium salt used in step S3) is selected from at least one of lithium oxide, lithium hydroxide, and lithium carbonate. The coprecipitation method in step S2) can be one of continuous coprecipitation, intermittent coprecipitation, or continuous-intermittent combined coprecipitation. In step S5), the mixing method of the granular pre-sintered semi-finished product and the lithium salt can be one of high-speed mixing, ball mixing, oblique mixing, plow mixing, and ribbon mixing; the crushing method used in step S4) can be mechanical crushing. Sintering is selected from one of primary sintering, secondary sintering, tertiary sintering, quadruple sintering, and quintuple sintering.

[0081] The effects of the present application are further demonstrated by specific examples and comparative examples.

[0082] Example:

[0083] A nickel-cobalt-boron positive electrode material is prepared according to the following steps:

[0084] (1) Matrix selection

[0085] The chemical formula of the nickel-cobalt-boron matrix is ​​Ni 0.8 Co 0.1 B 0.1 (OH)2, with a median particle size D50 of 10 μm, was purchased from GreenMe Company.

[0086] (2) Co(OH)2 precipitation is formed on the surface of the NiCoB matrix

[0087] A small amount of water, sodium hydroxide solution and ammonia solution were placed in the reactor as the base liquid, so that the pH value of the base liquid was 8 and the concentration of ammonia solution was 8g / L.

[0088] The nickel-cobalt-boron matrix is ​​placed in the bottom liquid in the reactor, and a cobalt salt solution, a sodium hydroxide solution and an ammonia solution are injected into the reactor respectively. During the process, the injection rate of the cobalt salt solution is controlled to be 30L / h, the pH value of the system is controlled to be 8 during the reaction, and the ammonia concentration in the system is controlled to be 8g / L. Co(OH)2 precipitation is formed on the nickel-cobalt-boron matrix. When the thickness of the Co(OH)2 precipitation reaches 50nm, the injection of the cobalt salt solution is stopped, the solid-liquid separation is performed, and the solution is washed and dried. After the solid-liquid separation, the matrix material coated with the Co(OH)2 precipitation is obtained.

[0089] (3) Preparation of sintered semi-finished cathode materials

[0090] The prepared matrix material coated with Co(OH)2 precipitate was mixed with lithium salt, the mass ratio of lithium salt to matrix material coated with Co(OH)2 precipitate was controlled to be 1.05, sintered at 500°C for 30h, and then sintered at 800°C for 30h to obtain a block sintered semi-finished positive electrode material.

[0091] (4) The block-shaped sintered semi-finished positive electrode material obtained in step (3) is crushed to obtain a granular pre-sintered semi-finished product with an inner layer of nickel cobalt lithium borate and a surface layer of lithium cobalt oxide.

[0092] (5) Preparation of sintered cathode materials

[0093] The granular pre-sintered semi-finished product was evenly mixed with 5000ppm cobalt B powder, and sintered at 800°C for 30h to obtain a sintered finished positive electrode material.

[0094] Comparative Example:

[0095] A method for preparing a nickel-cobalt-boron positive electrode material is prepared according to the following steps:

[0096] (1) Matrix selection

[0097] The chemical formula of the nickel-cobalt-boron matrix is ​​Ni 0.8 Co 0.1 B 0.1 (OH)2, particle size of 10 μm, purchased from GreenMe Company.

[0098] (2) Preparation of sintered semi-finished cathode materials

[0099] The nickel-cobalt-boron matrix material was mixed with lithium salt, the mass ratio of lithium salt to matrix was controlled to be 1.05, and the mixture was sintered at 500°C for 30 hours, and then sintered at 800°C for 30 hours to obtain a block-shaped sintered semi-finished positive electrode material.

[0100] (3) The block-shaped sintered semi-finished positive electrode material obtained in step (2) is crushed to form a granular pre-sintered semi-finished product.

[0101] (4) Preparation of sintered finished positive electrode materials

[0102] The granular pre-sintered semi-finished product was evenly mixed with 5000ppm zirconium oxide powder, and sintered at 800°C for 30h to obtain a sintered finished positive electrode material.

[0103] It can be seen from the preparation process of the embodiment that the nickel-cobalt-boron positive electrode material prepared in the embodiment includes an inner layer, a surface layer and a coating layer, the inner layer is nickel-cobalt lithium borate, the surface layer is lithium cobalt oxide, and the coating layer is lithium cobalt oxide. The median particle size D50 of the inner layer of nickel-cobalt lithium borate is about 10 μm.

[0104] From the preparation process of the comparative example, it can be seen that the nickel-cobalt-boron positive electrode material prepared in the comparative example includes an inner layer and a coating layer, the inner layer is nickel-cobalt lithium borate, and the coating layer is lithium zirconate. The median particle size D50 of the inner layer of nickel-cobalt lithium borate is about 10 μm.

[0105] The positive electrode sheet is made of the nickel cobalt borate positive electrode material prepared in the above embodiment, and is combined with the corresponding negative electrode sheet to form a lithium ion battery. This type of lithium ion battery is recorded as a first lithium ion battery. The positive electrode sheet is made of the nickel cobalt borate positive electrode material prepared in the above comparative example and is combined with the corresponding negative electrode sheet to form a lithium ion battery. This type of lithium ion battery is recorded as a second lithium ion battery. The difference between the first lithium ion battery and the second lithium ion battery is only the difference in the positive electrode material.

[0106] The high temperature cycle performance of the first lithium ion battery and the second lithium ion battery was tested according to GB / T 31484-2015. The test temperature was 45°C and the charge and discharge conditions were 1C / 1C. The high temperature storage recovery rate and high temperature storage retention rate of the first lithium ion battery and the second lithium ion battery were tested according to GB / T 31486-2024.

[0107] The first lithium-ion battery and the second lithium-ion battery are stored at high temperature. At 25°C, a DCR test is performed on the battery after 0.33C standard capacity at 50% SOC, the test rate is 2C, the test time is 30s, and (shelf end voltage-discharge end voltage) / discharge current is recorded as the discharge DCR at the current charge state.

[0108] Figure 1 : is a comparison diagram of high temperature cycle performance of the first lithium ion battery and the second lithium ion battery, wherein the dotted line is a schematic diagram of the cycle performance of the first lithium ion battery, and the solid line is a schematic diagram of the cycle performance of the second lithium ion battery.

[0109] Depend on Figure 1 It can be seen that under high temperature environment, the first lithium ion battery has a relatively high capacity retention rate for the same number of cycles; under the same capacity retention rate, the first lithium ion battery has a relatively high number of cycles. Therefore, the nickel cobalt lithium borate positive electrode material prepared in this application has relatively good cycle performance.

[0110] Figure 2 3 is a comparison diagram of the high temperature storage retention rate of the first lithium ion battery and the second lithium ion battery, wherein the dotted line is a schematic diagram of the high temperature storage capacity retention rate of the first lithium ion battery, and the solid line is a schematic diagram of the high temperature storage capacity retention rate of the second lithium ion battery.

[0111] Depend on Figure 2 It can be seen that the storage retention rates of the first lithium-ion battery and the second lithium-ion battery have basically the same changing trends as the high-temperature storage time increases, but the difference is that for the same storage time, the first lithium-ion battery has a higher capacity retention rate.

[0112] Figure 33 is a comparison diagram of the high temperature storage capacity recovery rate of the first lithium ion battery and the second lithium ion battery, wherein the dotted line is a schematic diagram of the high temperature storage capacity recovery rate of the first lithium ion battery, and the solid line is a schematic diagram of the high temperature storage capacity recovery rate of the second lithium ion battery.

[0113] Depend on Figure 3 It can be seen that the capacity recovery rate of the first lithium-ion battery and the second lithium-ion battery has basically the same changing trend with the increase of high-temperature storage time, but the difference is that for the same high-temperature storage time, the first lithium-ion battery has a higher capacity recovery rate, and after more than 80 days of high-temperature storage, its capacity recovery rate can reach 98%.

[0114] Figure 4 : is a comparison diagram of the high temperature storage internal resistance change of the first lithium ion battery and the second lithium ion battery, wherein the dotted line is a schematic diagram of the high temperature storage internal resistance change of the first lithium ion battery, and the solid line is a schematic diagram of the high temperature storage internal resistance change of the second lithium ion battery.

[0115] Depend on Figure 4 It can be seen that, compared with the second lithium-ion battery, the first lithium-ion battery has substantially the same internal resistance variation trend as the high-temperature storage time increases, but the difference is that, for the same storage time, the first lithium-ion battery has a smaller internal resistance.

[0116] From the above test results, it can be seen that the nickel-cobalt-boron positive electrode material provided by the present application, that is, the nickel-cobalt-boron positive electrode material includes an inner layer, a surface layer and a coating layer, the inner layer is nickel-cobalt-borate lithium, the surface layer is lithium cobaltate, and the coating layer is lithium cobaltate. The positive electrode material of this structure is relative to the existing nickel-cobalt-boron positive electrode material provided in the comparative example, which helps to improve the high temperature performance of lithium-ion batteries, helps to increase the cycle life of lithium-ion batteries, and helps to reduce the internal resistance of lithium-ion batteries.

[0117] Furthermore, since the difference between the first lithium-ion battery and the second lithium-ion battery is only the difference in the positive electrode material, the improvement in high temperature performance and the reduction in internal resistance of the first lithium-ion battery relative to the second lithium-ion battery are caused by the difference in the positive electrode material. It can be inferred that the nickel cobalt borate lithium positive electrode material provided in the present application has better high temperature performance and lower interface impedance.

Claims

1. A nickel-cobalt-lithium borate positive electrode material, characterized in that: include: A body, the body comprising an inner layer and a surface layer, the material of the inner layer is lithium nickel cobalt borate, and the material of the surface layer is lithium cobalt oxide; The coating layer is wrapped around the surface of the surface layer, and the material of the coating layer is lithium cobalt oxide.

2. The nickel-cobalt-lithium borate positive electrode material according to claim 1, characterized in that: The median particle size D50 of the inner layer is 2-15 μm.

3. The nickel-cobalt-lithium borate positive electrode material according to claim 2, characterized in that: The thickness of the surface layer is 1-100 nm.

4. The nickel-cobalt-lithium borate positive electrode material according to claim 2 or 3, characterized in that: The coating layer has a thickness of 1-100 nm.

5. A method for preparing a nickel-cobalt-lithium borate positive electrode material, characterized in that: The following steps are involved: S1) provides a nickel-cobalt-boron matrix with a molecular formula of Ni x Co y B z (OH)2, x+y+z=1; S2) forming Co(OH)2 on the surface of the nickel-cobalt-boron substrate; S3) using a substance with a surface layer of Co(OH)2 and an inner layer of a nickel-cobalt-boron matrix as a precursor, mixing the precursor with an excess of lithium salt, and pre-sintering the precursor to form nickel-cobalt-borate lithium borate in the inner layer and lithium cobalt oxide in the surface layer, and the product is in a block shape; S4) crushing the block product obtained in step S3) to obtain a granular pre-sintered semi-finished product with an inner layer of nickel cobalt lithium borate and a surface layer of lithium cobalt oxide; S5) mixing the product obtained in step S4) with a cobalt salt and sintering the mixture, so that the cobalt salt reacts with the lithium salt remaining on the surface of the granular pre-sintered semi-finished product, thereby forming a coating layer of lithium cobaltate on the surface of the granular pre-sintered semi-finished product.

6. The method for preparing the nickel cobalt lithium borate positive electrode material according to claim 5, characterized in that: In step S2), the method used to form Co(OH)2 on the surface of the nickel-cobalt-boron substrate is a co-precipitation method.

7. The method for preparing the nickel cobalt lithium borate positive electrode material according to claim 6, characterized in that: In step S2), the cobalt salt used to form the Co(OH)2 includes at least one of CoCl2·6H2O, Co(CH3COO)2·4H2O, CoCO3, Co(NO3)2·6H2O, CoSO4·7H2O, CoO, Co2O3, Co3O4, Co(OH)2, and CoC2O4.

8. The method for preparing the nickel cobalt lithium borate positive electrode material according to claim 6, characterized in that: In step S2), the precipitant used in the co-precipitation method includes at least one of KOH, NaOH, LiOH or ammonia water.

9. The method for preparing the nickel cobalt lithium borate positive electrode material according to claim 5, characterized in that: In step S5), the cobalt salt is at least one of Co(CH3COO)2·4H2O, CoCO3, Co(NO3)2·6H2O, CoSO4·7H2O, CoO, Co2O3, Co3O4, Co(OH)2, CoC2O4, and MgCo(OH)4.

10. The method for preparing the nickel cobalt lithium borate positive electrode material according to claim 5, characterized in that: In step S2), the coating thickness of Co(OH)2 is 1-100nm.